Reinventing virtual care: Bridging the healthcare system and citizen silos to create an integrated future. Issue 3 (May 2022) - Borycki, Elizabeth M.; Kushniruk, Andre W.
The pandemic has accelerated the move to virtual care. This has included remote monitoring and implementation of technologies that allow for patient care at home and assisted living for ageing in place. Technologies are available to help consumers to maintain their health and wellness. However, challenges associated with implementing virtual care remain. In this article, we describe some of these challenges, along with the need to develop new models for promoting effective and sustainable virtual care. This includes the need for integration of institutional efforts (eg, government and hospital) with emerging access to commercially available home technologies supplied to patients and citizens. The authors argue that consideration of a personal digital ecosystem and its relation to institutional digital health ecosystems is critical. The authors suggest virtual care be considered in the combined context of the person and healthcare system. Implications for future research directions for virtual care are discussed.